Prevalencia de Echinococcus granulosos en bovinos del centro de faenamiento municipal del cantón Latacunga - Tovar Herrera, Diego Steeven (2021)
In this research project, a review of the presence of Echinococcus granulosus in cattle is made, in order to determine the prevalence in animals arriving at the municipal slaughter center of Latacunga. For this purpose, the animals that entered in the month of June 2021 were taken into account, in order to collect samples and, if positive, to locate their origin. The research project has a quantitative approach, since it is expected to analyze and obtain results from a certain group of animals from a defined place. The technique of observation of macroscopic lesions in the affected organs (liver, lungs) of cattle from the municipal slaughtering center of Latacunga was proposed for the collection of samples. Thirty-three samples with macroscopic lesions were collected from cattle from the city of Latacunga and Salcedo. These samples were placed in sterile wide-mouth plastic bottles for transport to the veterinary clinic "CanVet", which has a laboratory and specialized equipment for the observation of microorganisms. The prevalence of Echinococcus granulosus in the 28 samples obtained from cattle from the city of Latacunga was 0%, since the lesions present in the affected organs were caused by other types of parasites. The remaining 5 samples from cattle from the city of Salcedo gave a prevalence of 0% for Echinococcus granulosus, since the results obtained were positive for Fasciola hepática.